(untitled) (Journal of Engineering, 2025)
Bearing capacity of soil is one of the important matters that occupies the minds of geotechnical engineers, especially in weak soils. In the field of geotechnical engineering, soil improvement is one of the most commonly used techniques. However, difficulties in implementation and increased costs have also caused scientists to look for more efficient and effective techniques. Many researchers as one of the innovative and promising alternatives have identified using skirts beneath shallow foundations in recent years. Their research has demonstrated the effectiveness of this method in treating the condition of the soil beneath the foundation, including enhancing bearing capacity vertically and laterally by 470% and 6.6 times, respectively, and reducing settlements by 186% and reducing rotation, slipping, and the shallow foundation’s uplift capacity by 397.7% on diverse soil types. For offshore constructions such as jack-up unit structures, wind turbine foundations, oil and gas plants, tension leg platforms, bridge foundations, and transmission towers, it was discovered that skirted foundations might be a formidable rival to conventional foundation types. The results obtained from this review indicate that there are many methods for improving problematic soils to increase their bearing capacity, uplift capacity, and reduce settlement, but all of these methods are largely related to the economic aspect and the feasibility of their implementation on-site. This study demonstrated that the use of skirting is very cost-effective, as it is a successful alternative to deep foundations in problematic soils and offshore conditions. In addition, the effectiveness of a skirt depends on factors such as length, depth, relative density, and its suitability for various soil types (e.g., sandy, clayey, liquefiable, and gypseous). Optimal skirt depth-to-width ratios improve the stability of foundations exposed to inclined and lateral loads.